3D skin bioprinting: future potential for skin regeneration - Pasierb, Anna; Jezierska, Marta; Karpuk, Aleksandra; Czuwara, Joanna; Rudnicka, Lidia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Skin provides protection against external agents and plays an essential role in maintaining the body homeostasis. Bioprinting as a novel strategy involves computer-controlled deposition of cells and scaffolds into a three-dimensional (3D) construction of skin. 3D bioprinting gives an opportunity to generate multi-layered vascularized skin grafts that can overcome the limitations of current skin substitutes. The main indication is treatment of troublesome wounds, especially severe burns and non-healing chronic lesions. Bioprinted skin equivalents offer a promising approach in the field of regenerative medicine. This review presents and discusses 3D skin construct formation, its limitations and modifications, and its usefulness.